2014
DOI: 10.1103/physreva.90.012516
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Casimir interactions for periodic surface-relief gratings using theCmethod

Abstract: We develop a formalism to calculate the fluctuation-induced interactions in periodic systems. The formalism, which combines the scattering theory with the C method borrowed from electromagnetic gratings studies, is suitable and efficient for the calculation of the Casimir forces involving surface relief gratings. We apply the developed technique to obtain the energy and lateral force for simple 1-D sinusoidal gratings. Using this formalism we derived known asymptotic expressions that were previously obtained t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In the spirit of a manipulation thourgh geometrical properties, structured surfaces have been the topic of many theoretical investigations. More specifically, by considering both 1D and 2D periodic gratings, both the radiative heat transfer [30][31][32][33][34][35][36][37] and the Casimir force at and out of thermal equilibrium [38][39][40][41][42][43][44][45][46][47] have been studied by employing a variety of theoretical approaches. It has been shown that gratings represent indeed a tool to modify, both by reducing and amplifying, radiative heat transfer, as well as to influence its spectral properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the spirit of a manipulation thourgh geometrical properties, structured surfaces have been the topic of many theoretical investigations. More specifically, by considering both 1D and 2D periodic gratings, both the radiative heat transfer [30][31][32][33][34][35][36][37] and the Casimir force at and out of thermal equilibrium [38][39][40][41][42][43][44][45][46][47] have been studied by employing a variety of theoretical approaches. It has been shown that gratings represent indeed a tool to modify, both by reducing and amplifying, radiative heat transfer, as well as to influence its spectral properties.…”
Section: Introductionmentioning
confidence: 99%
“…One particularly appealing application is to the case of periodic gratings, where both lateral and perpendicular forces can be measured [1][2][3][4][5]. On the theoretical side, one can use Rayleigh expansion methods for rectangular [6] and lamellar [7][8][9] gratings, C methods [10], and perturbative methods [11][12][13] to calculate Casimir interaction energies of periodic dielectrics or conductors. These approaches are often limited in their ability to handle deep corrugations [14][15][16][17][18][19][20] (for perfectly conducting rectangular corrugations, one can obtain exact results using path integral techniques [21,22]).…”
Section: Introductionmentioning
confidence: 99%